Pengembangan Video Pembelajaran IPA Energi Alternatif Kelas IV Sekolah Dasar - Muhammad Maulana Rofikhi; Wawan Priyanto; Ervina Eka Subekti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The background that drives this research is that teachers do not use media in learning to support learning skills and innovation in following the learning contained in the 2013 curriculum. alternative grade IV in Elementary School. This research was conducted at SD Negeri Giling 02 and MI Miftahul Ulum Karangkonang. The research subjects were students at SD Negeri Giling 02 and MI Miftahul Ulum. This study uses a research and development methodology that is used to produce certain products and test the feasibility of the products developed. The data in this study were obtained through questionnaires and interviews. The result of the analysis of this research is to produce a video media product for science learning materials for alternative energy for class IV in elementary schools. The results of the validation of the media expert's assessment get an average percentage of 93%, material experts get an average percentage value of 93%, the average value of the percentage of teacher responses is 98% and the average value of student responses is 100%. The conclusion of the science learning video media product for class IV alternative energy materials developed is very valid and practical to use in the learning process.